Assessment of the relative influences of long-range transport, fossil fuel and biomass burning from aerosol pollution under restricted anthropogenic emissions: A national scenario in India. (15th June 2021) - Dutta, Monami; Chatterjee, Abhijit
Abstract: The present study was conducted with the purpose to understand the spatial heterogeneity and the inter-state variability of the relative contributions of the long-range transport, fossil fuel and biomass burning on the atmospheric aerosol pollution across India. Satellite and reanalysis datasets (MODIS and MERRA-2) were used to study the total aerosol and its differential components over each of the Indian states under the limited anthropogenic emission condition (April 2020) and compared with the normal condition (April 2015–2019). We observed that the changes in aerosol pollution with the changes in sources from normal to limited anthropogenic activities were not homogeneous across the country. Based on such heterogeneity in "aerosol source-aerosol pollution" relationship, we divided the entire country in four different groups. The states under Group 1 (most of Indo-Gangetic Plain, north-eastern and parts of western and southern India) are found to be mostly influenced by the local/regional anthropogenic sources. The sources other than the biomass burning are the most influential for the aerosol pollution over Group 2 states (Punjab, West Bengal, Rajasthan, Madhya Pradesh, Karnataka and Tripura). Both the biomass burning and long range transport are the major factors for Group 3 state, Telangana. Rest of the states (Group 4) exhibit the relative dominance of the regional and trans-boundary transport over local anthropogenic emissions. Relative influences of fossil fuel and biomass burning over each other and how it changed from the normal to limited activities have also been quantified for each of the states of different groups. The results from the study would be an input of immense importance for the policy makers building state-wise strategies in air pollution control in India. Graphical abstract: Image 1 Highlights: Aerosols anomalies were determined between COVID-19 lockdown and normal period. The "aerosol-loading" and "aerosol-source" relationship varied between the states. A novel method was adopted determining relative influences of anthropogenic sources. States were identified with relative influences of fossil fuel and biomass burning.